1992
DOI: 10.1111/j.1365-2990.1992.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of neurons containing somatostatin in the dentate hilus of the rat hippocampus after cerebral ischaemia, and a note on their commissural connections

Abstract: In a light microscopical study, we previously showed that more than 80% of somatostatin (SS) immunoreactive (-i) neurons in the hilus of the dorsal part of the rat dentate gyrus are lost 4 days after ischemia. In order to verify that the loss of SS immunostaining is due to an actual loss of the SS-i neurons and not merely a loss in expression of SS immunoreactivity, we have now performed an ultrastructural study of these neurons before and 40 h after 20 min of global cerebral ischaemia in adult rats. The norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…accumbens. Our experiment was a part of a larger study of all structures of the adult brain in hypoxia, which relied on previous research conducted by scientists such as Nytrai et al [6], Cho et al [10] Soriano et al [25], Xie et al [30] and Johansen et al [14], whose studies marginally presented results on cells of other (nonhippocampal) regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…accumbens. Our experiment was a part of a larger study of all structures of the adult brain in hypoxia, which relied on previous research conducted by scientists such as Nytrai et al [6], Cho et al [10] Soriano et al [25], Xie et al [30] and Johansen et al [14], whose studies marginally presented results on cells of other (nonhippocampal) regions.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in stress factors, neurotrophic and early genes in response to stress as a condition of mild stroke may indirectly prevent lethal ischemic insult by opening the adenosine triphosphate (ATP)-sensitive potassium channels [14]. The level of ATP, as the most important parameter for cell survival, directly affects the intensity of the stroke, and therefore the type of cell death caused by experimentally induced ischemia.…”
Section: The Role Of Proto-oncogenes and Their Importancementioning
confidence: 99%
“…At the electron microscopic level, the vulnerable SS-i neurons in hilus show ischemic cell changes (Brown and Brierley, 1972) with vacuolation of the endoplasmatic reticulum, and SS-i associated to the vacuolated membranes (Johansen et al, 1992). We rendered that vacuolation of the endoplasmatic reticulum made the SS-i neurons appear with intensified and homogeneously dispersed SS-i in the light microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first 2 d after ischemia, SS immunoreactive (-i) neurons in hilus disappear. These neurons display a more rapid maturation of the ischemic cell death than the CA1 pyramidal cells (Johansen et al, 1987(Johansen et al, , 1992. In addition, we have shown that neurons in hilus and the CA3 mossy fiber layer accumulate free zinc, in or on their cell bodies, shortly after ischemia (Tbnder et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Histološki posmatrano, naši nalazi potvrđuju nalaze Mizukave, Hendry-a i Yamasita o obliku neurona u kojima se opisuju mali, bipolarni i multipolarni neuroni [4,19,20,21]. U našim nalazima navodimo još oblik sferičnih, triangularnih i nepravilnih neurona i u kori, i u ostalim NPY-IR struk turama mozga.…”
Section: Diskusijaunclassified